A study in continuity - Tay, Tania Wen Jing (2018)
A Study in Continuity is an ongoing artistic investigation that explores continuity through time, image, space, motion and sound. Presented as a research collection of objects in motion, the study, which undertakes a poetic and pseudo-clinical nature, examines the perpetual motion of continuity, biological cycle of life and its demise: composite factors which echo the repetitiveness, and ongoingness of life itself.